Low Field Pediatric Brain Magnetic Resonance Image Segmentation and Quality Assurance: First MICCAI Challenge, LISA 2024, Held in Conjunction with MICCAI 2024, Marrakesh, Morocco, October 10, 2024, Proceedings - Lepore, Natasha; Linguraru, Marius George (Lecture Notes in Computer Science, 2025)
This open access LNCS volume 15515 constitutes the refereed proceedings of the First MICCAI Challenge on Low Field Pediatric Brain Magnetic Resonance Image Segmentation and Quality Assurance, LISA 2024, Held in Conjunction with MICCAI 2024, in Marrakesh, Morocco, in October 2024. The 6 full papers presented were carefully reviewed and selected from 8 submissions. This MICCAI Challenge focuses on the development and evaluation of automatic image analysis and machine learning algorithms and Ultra-low-field brain imaging has the potential to become a transformative tool for both clinical and research applications.